Self-perception of periodontal health status among individuals with Fanconi anemia - Nicole Nichele Perdoncini (Elsevier, 2021)
Introduction: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations and bone marrow failure. One of the most common oral diseases in individuals with FA is periodontitis and adequate self-perception of periodontal status could contribute to its prevention and early detection. Aim: To compare oral health self-perception, measured by a questionnaire, with the clinical oral condition of patients with FA. Methods and Results: Fifty-six patients with FA, over 11 years of age, answered a questionnaire about dental history and self-reported oral health. Decayed, missing, and filled teeth (DMFT), Visible Plaque Index (VPI) and Gingival Bleeding Index (GBI) were measured. The median age of participants was 21 years (min 11, max 44), 31 (55%) were females and 25 (45%) males. Thirty-five (62.5%) participants rated their oral condition as satisfactory and 7 (12.5%) participants reported tooth mobility, 10 (17.9%) exposed roots and 21 (37.5%) gingival bleeding. Clinical examination detected average DMFT = 5.23, VPI = 31.36% and GBI = 33.77%. The gingival bleeding report was more frequent among individuals with higher GBI (p =  0.014). The DMFT was higher in those who had already undergone dental treatments (p =  0.031). There was an association between participants who presented dental caries and who rated their oral health as poor (p =  0.03). The question “Do your gums bleed easily?” had good accuracy in the evaluation of periodontal disease (p =  0.68). Conclusion: Oral health self-perception of individuals with FA about gingival inflammation was associated with their gingival bleeding index.